2016
DOI: 10.1007/s12035-016-9815-4
|View full text |Cite
|
Sign up to set email alerts
|

RIT2 Polymorphisms: Is There a Differential Association?

Abstract: Neurological disorders include a wide variety of mostly multifactorial diseases related to the development, survival, and function of the neuron cells. Single-nucleotide polymorphisms (SNPs) have been extensively studied in neurological disorders, and in a number of instances have been reproducibly linked to disease as risk factors. The RIT2 gene has been recently shown to be associated with a number of neurological disorders, such as Parkinson's disease (PD) and autism. In the study reported here, we investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 53 publications
0
33
0
Order By: Relevance
“…Recent findings of a link between the low-frequency alleles at the extreme short and long ends of "exceptionally long" STRs with human disorders [5][6][7] Fig. 8.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent findings of a link between the low-frequency alleles at the extreme short and long ends of "exceptionally long" STRs with human disorders [5][6][7] Fig. 8.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously reported that approximately 2% of the human protein-coding genes contain STRs of ≥6 repeats in the critical core promoter region [3]. Preliminary findings indicate that expansion of a number of these STRs may be linked to adaptive evolutionary processes in human, and also endure the burden of certain human disorders such as schizophrenia, bipolar disorder, and Alzheimer's disease [4][5][6][7].…”
Section: Introductionmentioning
confidence: 92%
“…Recent GWAS studies reported Rit2 as a risk allele for several DA-associated disorders, including PD, ET, ASD, schizophrenia, and bipolar disorder [14]. The link between Rit2 expression and schizophrenia is particularly interesting.…”
Section: Rit2 Expression Increases Throughout Postnatal Development Amentioning
confidence: 99%
“…The link between Rit2 expression and schizophrenia is particularly interesting. A recent report examining genome-wide human 5' short tandem repeats (STRs) found that the RIT2 locus has among the longest GA-STRs in humans, at 11 repeats, and that increased STR length drives increased Rit2 expression [14]. Moreover, a 5/5 STR Rit2 variant was identified in a proband with profound early onset psychoses, raising the possibility that decreased Rit2 expression may be linked to schizophrenia.…”
Section: Rit2 Expression Increases Throughout Postnatal Development Amentioning
confidence: 99%
See 1 more Smart Citation